2010
DOI: 10.1074/jbc.m109.080770
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Plasmodium falciparum Apical Membrane Antigen 1 and the Rhoptry Neck Protein Complex Defines a Key Step in the Erythrocyte Invasion Process of Malaria Parasites

Abstract: Invasion of host cells by apicomplexan parasites, including Plasmodium falciparum and Toxoplasma gondii, is a multistep process. Central to invasion is the formation of a tight junction, an aperture in the host cell through which the parasite pulls itself before settling into a newly formed parasitophorous vacuole. Two protein groups, derived from different secretory organelles, the micronemal protein AMA1 and the rhoptry proteins RON2, RON4, and RON5, have been shown to form part of this structure, with antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
265
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 231 publications
(280 citation statements)
references
References 45 publications
11
265
1
3
Order By: Relevance
“…They were also colocalized on the surface of free merozoites, although PfMSPDBL2 appeared to be more concentrated at the apical end of the cell as indicated by its close apposition to RON4, a protein located in the neck of the rhoptries (Fig. 2C, bottom row) (37). This confirmed previous work showing that PfMSPDBL1 was located on the merozoite surface and also demonstrated that PfMSPDBL2 had a similar localization consistent with them having similar functions (14).…”
Section: Pfmspdbl2 Is a Red Cell-binding Protein On The Merozoitesupporting
confidence: 79%
“…They were also colocalized on the surface of free merozoites, although PfMSPDBL2 appeared to be more concentrated at the apical end of the cell as indicated by its close apposition to RON4, a protein located in the neck of the rhoptries (Fig. 2C, bottom row) (37). This confirmed previous work showing that PfMSPDBL1 was located on the merozoite surface and also demonstrated that PfMSPDBL2 had a similar localization consistent with them having similar functions (14).…”
Section: Pfmspdbl2 Is a Red Cell-binding Protein On The Merozoitesupporting
confidence: 79%
“…(9)(10)(11). AMA1 has similar topology with TRAP/MIC2 with its bulky ectodomain binding to rhoptry neck proteins (RONs) that are secreted from the rhoptries and inserted into host plasma membrane to mediate formation of a moving junction between the host and parasite membranes (12)(13)(14)(15). The cytoplasmic tail of AMA1 (AMA1t) also binds rabbit ALD in vitro, and a TgAMA1 mutant with a pair of aromatic residues changed to alanines (i.e., F547A, W548A) disrupts aldolase binding in vitro and blocks host-cell invasion (16).…”
mentioning
confidence: 99%
“…The roles of MICs (TgMIC8, PfEBA175 and PfAMA1) in the process leading to the secretion by the rhoptry organelles (Kessler et al, 2008;Richard et al, 2010;Singh et al, 2010) is an exiting new aspect of receptor-ligand interactions in apicomplexans and of the mechanism of host cell invasion. Molecular genetic studies in Plasmodium and Toxoplasma suggest that signal transduction is likely mediated by the cytoplasmic domains of these MICs (Gilberger et al, 2003;Treeck et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Microneme proteins (MICs) are key mediators of cytoadherence, but also play other essential and non-overlapping roles in the invasion process (Carruthers and Tomley, 2008;Soldati-Favre, 2008). Notably, recent studies have highlighted the roles of MICs (TgMIC8 in Toxoplasma gondii; PfEBA175 and PfAMA1 in Plasmodium falciparum) in the process leading to secretion by the rhoptries (Kessler et al, 2008;Richard et al, 2010;Singh et al, 2010).…”
Section: Mechanism Of Invasion and Role Of Adhesinsmentioning
confidence: 99%